2000
DOI: 10.1002/chin.200032242
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Recent Advances in the Field of Camouflaged Carboranes and Polyhedral Boranes

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This work is the first venture into the area of B-methylation chemistry of compounds derived from closo -1,2-H 2 C 2 B 8 H 8 ( 2a ). It was demonstrated that all B-positions in 2a can be furnished with methyl substituents to give closo -1,2-H 2 C 2 B 8 Me 8 ( 2c ) or closo -1,2-H 2 C 2 B 8 Me 7 X ( 2g – 2j ) carboranes via electrophilic reaction with MeI, in contrast to the bigger, 12-vertex 1,2- and 1,7-R 2 C 2 B 10 H 10 analogs in which two boron sites remain unmethylated. It was also shown that a similar B-permethylation of the 1,2-Me 2 C 2 B 8 H 8 ( 2b ) analog fails, most probably because of steric and electronic effects of the two adjacent CMe groups rather than for kinetic reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work is the first venture into the area of B-methylation chemistry of compounds derived from closo -1,2-H 2 C 2 B 8 H 8 ( 2a ). It was demonstrated that all B-positions in 2a can be furnished with methyl substituents to give closo -1,2-H 2 C 2 B 8 Me 8 ( 2c ) or closo -1,2-H 2 C 2 B 8 Me 7 X ( 2g – 2j ) carboranes via electrophilic reaction with MeI, in contrast to the bigger, 12-vertex 1,2- and 1,7-R 2 C 2 B 10 H 10 analogs in which two boron sites remain unmethylated. It was also shown that a similar B-permethylation of the 1,2-Me 2 C 2 B 8 H 8 ( 2b ) analog fails, most probably because of steric and electronic effects of the two adjacent CMe groups rather than for kinetic reasons.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, B-substitution processes on 2 pertinent to this work have so far been very scarce, being restricted to a few reactions with halogenation agents to afford 7-, 10-, and 7,10-substituted derivatives . Several successful B-methylation experiments in the monocarba- and dicarbaborane series, together with those achieved later by our group in the B-permethylation of the ten-vertex dicarbaboranes closo -1,6-C 2 B 8 H 10 , closo -1,10-C 2 B 8 H 10 , and arachno -6,9-C 2 B 8 H 14 , prompted us to extend boron-methylation strategy to the remaining closo -isomer 2 . Special attention will be paid to the permethylation of B-vertices and thermal rearrangement reactions under the formation of hydrocarbon–boron hybrid structures of egg shape that exhibit a surprisingly high stability .…”
Section: Introductionmentioning
confidence: 96%
“…In the current area, only one alkylated structure of 1 is available, namely, 1-Et- nido -B 10 H 13 . In addition to that, the list of iodo, and/or other halogeno (X) and trifluoromethylsulfonyl (OSO 2 CF 3 ), derivatives of 1 is limited to a few examples, e.g., the substituted lowest rim of 1 (i.e., I bonded either to B1 or to B2) and the substituted upper rim of 1 (i.e., H in B6 and/or B9 positions substituted with X or OSO 2 CF 3 , , and Br bonded to B5 and B10). , In view of the recent permethylation or persubstitution methods reported by our or other laboratories, we have now tried to extend these synthetic strategies to compound 1 , a key species of the borane series, also taking into account that the methylation of the boron clusters usually provides more stable species suitable for further examinations.…”
Section: Introductionmentioning
confidence: 99%
“…2 ) and those leading to a series of halo derivatives 1,10-H 2 C 2 B 8 H 7 -2-X. 6 The successful B-methylation experiments in the 12-vertex carborane series, 7–9 together with those achieved by our group in the B-methylation of closo -1,6-C 2 B 8 H 10 , 10 arachno -6,9-C 2 B 8 H 14 , 11 prompted us to extend boron-methylation strategy to the most stable members of the 10-vertex closo series, closo -1,10-R 2 C 2 B 8 H 10 (1) (where R = H or Me), which have been now relatively easily available. 12 In this article we would like to present electrophilic reactions with methylation agents leading to quantitative permethylation of B-vertexes under the formation of rigid, hydrocarbon–boron structures of egg shape that exhibit outstandingly high stability.…”
Section: Introductionmentioning
confidence: 99%